Trabalho e formação profissional: trabalhadores hiperqualificados à deriva - Jacobson, Ana Paula Mello (Universidade Federal de São Carlos, 2020)
This work sought to understand the subjective articulation that young people who attended higher education - undergraduate or graduate and, simultaneously, work in the informal market do between professional training, informal work and employment. Specifically, it intended: to investigate the meanings attributed to professional training, to investigate reasons and forms of insertion in informal work, as well as the routine and strategies defined to reconcile studies with work, and to understand the expectations and life project of these subjects. The method used was qualitative, through semi-structured interviews conducted with the participants, which were recorded and transcribed. The recruitment of participants took place using the snowball sampling technique. The analysis of the interviews was based on the thematic content analysis of the transcribed interviews, presented by Minayo, Deslandes & Gomes (2007). Four categories of analysis were highlighted from the transcripts of the interviews, which are: life project, course and academic experience, work, economic conditions and student assistance. It was possible to observe the dialectical nature of life projects, the influence of the socio-political-economic context on them, the variability of reasons why young people enter higher education and also the variability of reasons why they enter the world of informal work, the different forms of conciliation between study and informal work, the different impacts brought by informal work simultaneously with studies, and the importance of public student assistance policies.
Work and vocational training: hyper-skilled workers adrift
Keywords: Juventude; Trabalho Informal; Projeto de Vida; Curso Superior; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL